(untitled) (Gestão & Regionalidade, 2025)
The present study aims to measure the technical efficiency of the municipalities of the southeastern region of the state of Pará in the use of resources to provide health services. The research identified disparities between the levels of efficiency found, taking as reference the municipalities of the southeastern mesoregion of Pará. The method used to measure efficiency was the Data Envelopment Analysis. As results of the study it was noticeable the discrepancy between the degree of technical efficiency among the municipalities, being that of the 30 municipalities that comprised the sample of the study, 15 municipalities presented an excellent degree of efficiency, 10 municipalities obtained a degree of efficiency classified as good and 5 of the municipalities of the sample obtained a weak degree of efficiency. The study points out the need to create an institutional relationship network where managers can seek alternatives to exchange successful experiences in municipalities close to their context